A review of wheat diseases—a field perspective. (26th December 2017) - Figueroa, Melania; Hammond‐Kosack, Kim E.; Solomon, Peter S.
Summary: Wheat is one of the primary staple foods throughout the planet. Significant yield gains in wheat production over the past 40 years have resulted in a steady balance of supply versus demand. However, predicted global population growth rates and dietary changes mean that substantial yield gains over the next several decades will be needed to meet this escalating demand. A key component to meeting this challenge is better management of fungal incited diseases, which can be responsible for 15%–20% yield losses per annum. Prominent diseases of wheat that currently contribute to these losses include the rusts, blotches and head blight/scab. Other recently emerged or relatively unnoticed diseases, such as wheat blast and spot blotch, respectively, also threaten grain production. This review seeks to provide an overview of the impact, distribution and management strategies of these diseases. In addition, the biology of the pathogens and the molecular basis of their interaction with wheat are discussed.